PERBEDAAN ANTARA EKSTRAK ETANOL JAHE EMPRIT (Zingiber officinale var.Amarum), JAHE GAJAH (Zingiber officinale var.Officinarum), JAHE MERAH (Zingiber officinale var.Rubrum) DALAM MENGHAMBAT BAKTERI STREPTOCOCCUS MUTANS - Nur Dianawati; Manisha Rizki Zulfira (Bhakta Dental Journal, 2023)
Dental caries is a disease characterized by damage to the hard tissue of the teeth. Streptococcus mutans is a bacterium that causes caries. Plaque control is carried out mechanically and chemically. Therefore we need alternative natural ingredients such as emprit ginger, elephant ginger, red ginger which have antibacterial properties that can be used as Streptococcus mutans antibacterials. This study to find out the difference between extracts of emprit ginger, elephant ginger, red ginger in inhibiting bacterial growth and killing Streptococcus mutans bacteria. This study was an experimental laboratories with Post-test Only Control Group research design. The antibacterial method used is the dilution method. The treatment group consisted of extracts of emprit ginger, elephant ginger, red ginger concentrations of 5%, 10%, 15%, 90%. We found emprit ginger extract has MIC at a concentration of 10% and MBC at a concentration of 15%. MIC of elephant ginger extract at a concentration of 15% and MBC at a concentration of 90%. Red ginger extract has MIC at a concentration of 5% and MBC at a concentration of 10%. And there was differences between the extracts of emprit ginger, elephant ginger, and red ginger in inhibiting and killing Streptococcus mutans bacteria Keywords: Ginger Extract, Minimum Inhibitory Concentration (MIC), Minimum Bacteriosid Concentration (MBC), Streptoccocus mutans